Proportions and development of the head in children from Poznań - Malinowski, Andrzej (Anthropological Review, 1975)
In this paper results of investigations carried in 1971 - 72 on children in age 3-18 years are presented. Numerical characteristics of examined characters are given in table 1. Relative advancement in a state of development of particular characters, expressed in percentages of final value (for 18 years old individuals), is shown on figures 1-6. Sex differences in development of particular characters are illustrated on figures 7 - 9. Values of indices are given in table II. It was shown that examined characters have differently advanced development in early childhood, dynamics of their growth also varies causing changes with age in values of many indices. During the studied period of life head becomes longer with broader occiput and forehead as compared with maximum breadth, nose, total and upper face are lenghtened in relation to their breadths. Measures of breadth, especially these of neurocranium are more advanced developmentally in early childhood than length of head and face. In early childhood most advanced among all measurements of the face is breadth of forehead, somewhat less breadth of face and bigonial diameter. It was found that during last 50 years there is no acceleration in head development, only cephalic index slightly decreases in compared age groups. Moreover children from Poznan are more dolichocephal than individuals of the same age examined in Kraków by Jasicki and Sikora, they have also slightly broader faces. However in accordance with results obtained by Sikora during development lenghtening of the head is greater among brachycephalics than among dolichocephalics, hence dolichocephalization observed during development is more marked in children from Kraków than from Poznań. Furthermore of some interest is small adolescent growth spurt in characters of the head.